The oncogenic transformation of T51B rat liver epithelial cells alters their sensitivity to apoptotic stimuli. - Dhanraj, Karen Nalini. (University of Ottawa (Canada), 1998)
Rat liver non-parenchymal epithelial cells were stably transfected with the following plasmids: (i) pRSVNeo containing a neomycin resistance gene (Neo) under control of the Rous sarcoma virus (RSV) long terminal repeat element and (ii) pMT3 containing the Neo gene and the coding sequence of the polyoma middle T antigen (mT) under control of the SV40 enhancer region. Soft agar assays revealed no neoplastic transformation of cells expressing pRSVNeo plasmids, however overexpression of pMT3 plasmids generated a highly tumorigenic cell line. Two approaches were used to induce apoptosis in these cell lines, i.e. serum withdrawal and treatment with a chemotherapeutic drug, teniposide (VM26). The Neo cells were resistant to serum deprivation and sensitive to the VM26 treatment. In contrast, the highly transformed mT cells were very sensitive to the lack of growth factors but became extremely resistant to the VM26 treatment. These cells could arrest their growth and survive for 2 days in the presence of 10 $\mu$M VM26. Under the same experimental conditions, the viability of Neo cells dropped and they could only survive for a few hours. Analysis of several growth arrest and DNA-repair related proteins was performed and correlated with the cells' responsiveness to apoptosis. For example, in the VM26-resistant mT cells, the level of DNA repair-associated proteins was upregulated in response to the drug treatment. The results of this study clearly demonstrated that the mT protein brought about cellular phenotypic and metabolic changes, manifested not only as tumorigenic transformation, but also as a resistance to treatment with the chemotherapeutic drug, VM26.
Keywords: Biology, Cell.